Ontological-functional Status of the Nation and the Basic Ideas of Liberalism and Communitarianism - Kieliszek, Zdzisław (Studia Warmińskie, 2017)
In the article the concept of the nation is related to the ideals of liberalism and communitarianism. There are also compactly presented liberalism and communitarianism. There is also described ontological and functional status of the nation, which is a natural community to guarantee human freedom and ability to realize itself as a social being. On the basis of analysis, the author comes to the conclusion that the adherents of liberalism and communitarianism should appreciate the phenomenon of the nation. This means that the proponents of liberalism, in the name of the implementation of its basic idea of protecting human freedom, should replace an inherent aversion to various forms of society, which are usually perceived as a threat of human freedom, by supporting the development of different nations. While Communitarians, emphasizing the role of the different forms of society in human life, should support the nation, because it has a special role in the human mode of being, which can not have other form of society.